Визначення опорних точок у процесі планування моніторингу водяного середовища - Чесноков, В.І.; Світлична, В.А.; Савкова, О.Й. (Фізико-механічний інститут ім. Г.В. Карпенка НАН України, 2010)
In the article the design of fiducial points definition algorithm for optimal rote planning of aqueous medium parameters monitoring conduction is considered, the model of the algorithm realization is given.